(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article examines the problems of translation and equivalence, especially cultural expressions that present national customs and traditions. Cultural terms usually cause fewer problems. This article describes in detail the national and cultural specifics of translating works of Uzbek classical literature into English.